2002
DOI: 10.1007/s11661-002-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

Solidification thermal parameters affecting the columnar-to-equiaxed transition

Abstract: Experiments were conducted to analyze the columnar-to-equiaxed transition (CET) during the upward unsteady-state directional solidification of Al-Cu and Sn-Pb alloys, under different conditions of superheat and heat-transfer efficiencies at the metal/mold interface. A combined theoretical and experimental approach is developed to quantitatively determine the solidification thermal parameters: transient heat-transfer coefficients, tip growth rates, thermal gradients, and cooling rates. The observed results do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
2
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 26 publications
(22 reference statements)
5
79
2
9
Order By: Relevance
“…So such an experiment can be useful for validation of diffusion-only models, such as the present one under discussion. The authors had previously 26) carried out a similar study on Al-Cu alloys, which also solidify with minimum convection if chilled unidirectionally from the bottom.…”
Section: Comparison Of Predictions With Experimentsmentioning
confidence: 99%
“…So such an experiment can be useful for validation of diffusion-only models, such as the present one under discussion. The authors had previously 26) carried out a similar study on Al-Cu alloys, which also solidify with minimum convection if chilled unidirectionally from the bottom.…”
Section: Comparison Of Predictions With Experimentsmentioning
confidence: 99%
“…According to this list in table 1, it seems that cooling rate is not sensitive to the position of the CET. On the other hand, the response of The thermal CET criteria are recognized as very good indicative for the macrostructural transition as reported in several articles [12][13][14]17,18 . However, none previous study has been found on determining the solidification thermal parameters associated with the CET of cast iron.…”
Section: Resultsmentioning
confidence: 81%
“…However, none previous study has been found on determining the solidification thermal parameters associated with the CET of cast iron. In the case of Sn-based 12,13,19 and Al-based 14,17,18 alloys investigations have been addressed to single-phase and hypoeutectic alloys. In these cases, critical cooling rate was established as a realistic criterion, since cooling rate (Ṫ) encompasses growth rate (V) and temperature gradient (G), i.e., =G x v. The present investigation deals with a eutectic alloy and in this case it appears that a critical growth rate of about 0.6mm/s is adequate criteria for cast iron.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30) In the present casting, it is possible that the unstable contact condition between the growing shell and the roll surface fluctuates G/R value, and the fluctuation triggers a structure transition from columnar to equiaxed grain. 31) There are several possibilities to produce the unstable contact condition. The solidification of the transition zone takes place before constructing the stable melt pool level in the nozzle.…”
Section: Formation Of Grain Structurementioning
confidence: 99%